Fertilisation Methods for Commercial Yield in Three Garlic Cultivars (Allium sativum L.) - Condor, J. (2019)
Garlic (Allium sativum L.) is an important crop for domestic consumption in Peru. However, there is insufficient information available on crop management, particularly on fertiliser application to local cultivars. In order to evaluate the response of three garlic cultivars to three fertilisation methods, an experiment was conducted at the Donoso Experimental Station in Huaral district, a province of Lima. Three garlic cultivars were used as experimental materials: ‘Cincomesino’, ‘Arequipeño 14’ and ‘Margosino’. Three methods of fertilisation were applied as treatments: broadcast application before furrowing (M1), fertilisation in a superficial groove or false furrow (M2), and fertilisation in the lateral furrows, or band application (M3). The experiments were installed in three parcels for each cultivar, with a randomised complete block design for each parcel and four replications. In general, localised fertilisation methods showed the best performance for the broadcast method. Regarding total yield, fertilisation at the sides of the furrow (M3) for ‘Cincomesino’ reached 13.08 t/ha. The highest yield for the ‘Arequipeño 14’ cultivar (12.25 t/ha) was achieved using fertilisation with a surface groove or false furrow (M2). For the ‘Margosino’ cultivar, fertilisation on the sides of the furrow was ideal, and the yield was 10.95 t/ha.